PENGARUH PENDAPATAN ORANG TUA DAN KETERSEDIAAN SARANA BELAJAR TERHADAP MOTIVASI BELAJAR DAN DAMPAKNYA PADA HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS XI IPS SMAN 1 KOTO KAMPAR HULU - Andriyani, Septi; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is conducted in SMAN 1 Koto Kampar Hulu with the aim to explain (1) the direct influence of parents' income on learning motivation, (2) direct influence of the availability of learning facilitiesto learning motivation, (3) direct influence of learning motivation toward learning achievement, (4) ) The direct influence of the parents' income on the learning achievement, (5) the direct influence of the availability of learning facilities on the learning achievement. Data were collected by questionnaire from 70 students, the technique of data analysis was done by path analysis. The result of research are: (1) there is direct influence of parent income to learning motivation equal of 0,019 (2) there is direct influence of availability of learning facilitiesto learning motivation equal to 0,028 (3) there is direct influence of learning motivation to learning achievementof 0.000 (4) Direct income of parents to learning achievementof 0.048 (5) there is a direct influence of the availability to learning facilities on learning achievementof 0.005Keywords: income parents,the availability of learning facilities, Learningmotivation, learning achievement